2014
DOI: 10.1364/ao.53.006332
|View full text |Cite
|
Sign up to set email alerts
|

Control of mid-spatial frequency errors considering the pad groove feature in smoothing polishing process

Abstract: Mid-spatial frequency error (MSFR) should be strictly controlled in modern optical systems. As an effective approach to suppress MSFR, the smoothing polishing (SP) process is not easy to handle because it can be affected by many factors. This paper mainly focuses on the influence of the pad groove, which has not been researched yet. The SP process is introduced, and the important role of the pad groove is explained in detail. The relationship between the contact pressure distribution and the groove feature inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A pitch lap tool is often made to match the form of optics due to its viscoelastic property. 11 To achieve better matching and proper hardness of the pitch lap tool, we use the combination of Gugolz #64 and #73 pitches. Aluminum or brass plates with a centered hole are chosen as the base of the pitch tools.…”
Section: Fabrication Parametersmentioning
confidence: 99%
“…A pitch lap tool is often made to match the form of optics due to its viscoelastic property. 11 To achieve better matching and proper hardness of the pitch lap tool, we use the combination of Gugolz #64 and #73 pitches. Aluminum or brass plates with a centered hole are chosen as the base of the pitch tools.…”
Section: Fabrication Parametersmentioning
confidence: 99%
“…Among them, the surface waviness error of key optical components leads to an obvious peak intensity, which might damage the optical components [4]. In addition, the surface roughness of optical components affects imaging clarity, particularly around focal points.…”
Section: Introductionmentioning
confidence: 99%
“…With the parametric model, Kim compared the smoothing factors of different polishing tools, finding that the elastic material with harder surface had better smoothing effect [18]. Nie found that the polishing pad groove did affect the material removal and also the radial slotting method had a better smoothing effect by changing the slotting method of the polishing pad groove [19].…”
Section: Introductionmentioning
confidence: 99%